Clinical Presentation and Outcome of Five Neonates With Enterovirus Central Nervous System Infection: Contrasting One Kawasaki-Like Case With Cardiac Involvement and Seizures With Four Benign Cases - Alina Peternell; Christopher Schödl; Irena Odri Komazec; Matthias Baumann; Christian Lechner (Case Reports in Pediatrics)
Conclusions: In neonates who appear septic without an apparent focus, EV CNS infection should be considered and can be diagnosed by CSF PCR testing. Diagnosis leads to earlier discontinuation of antibiotic treatment and shorter hospital stay. Neonates with EV infection should be screened for cardiac complications and in severe cases treated with IVIG. CSF abnormalities might predict a more severe disease course and justify closer monitoring.